Municipal waste recycling in the EU: a multi-method analysis of determinants and country profiles (2005–2023) - Cehlár, Michal; Taušová, Marcela; Ivanková, Viera; Khouri, Samer (Frontiers in Environmental Science, 2025)
IntroductionMunicipal waste recycling plays a central role in European Union’s (EU) transition to a circular economy and in meeting long-term sustainability goals. Identifying key macro-level drivers of recycling outcomes remains essential for effective policy development.MethodsThe study aimed to examine the macro-level determinants of municipal waste recycling in EU countries over the period 2005–2023, and to identify country groupings based on shared characteristics. The dependent variable was the municipal waste recycling rate, while independent variables included real gross domestic product (GDP) per capita, urban population size, environmental tax revenues, government expenditures on environmental protection, government budget allocations for R&D (GBARD) directed at environmental objectives, and private investment in circular economy sectors. The analysis employed multiple linear regression with backward elimination to identify statistically significant predictors of recycling performance. Temporal patterns were assessed using a simple linear trend analysis. Ward’s hierarchical clustering based on five-year averages was conducted to group countries with similar characteristics.ResultsRecycling rates varied substantially across countries and time, with the EU average reaching 33.29%. A positive and statistically significant trend was observed over time; however, only a small group of countries exceeded the EU’s 2025 target (55%). Regression analysis revealed that higher recycling rates were statistically associated with real GDP, environmental tax revenues, private investment in circular economy sectors, and GBARD (% GDP). Interestingly, urban population size and government expenditures on environmental protection (% GDP) were negatively associated with recycling rates, possibly reflecting structural pressures in densely populated areas and inefficiencies in public spending. GBARD expressed as a share of total GBARD also showed a negative relationship, possibly reflecting time lags between research funding and observable effects. One of the more advanced clusters included Germany, France, Italy, and Spain, which combined high recycling rates with strong economic and investment profiles. The least performing cluster, comprising Bulgaria, Estonia, Lithuania, Croatia, Poland, Malta, and Cyprus, was characterized by low recycling outcomes alongside less favorable economic and institutional conditions.DiscussionThe findings underscore the need for differentiated fiscal and investment strategies, improved efficiency in public spending, and tailored support for countries facing demographic or infrastructural challenges.